In vitro Multiplication of Vegetable Crop in Brinjal Solanum melongena L - Jagatheeswari, D (International Journal of Pharmaceutical & Biological Archive, 2014)
In vitro Multiplication of Vegetable Crop in Brinjal Solanum melongena L